An Empirical Analysis of Money Demand and Monetary Policy Under Islamic Banking - Ramin Cooper Maysami; Mong Wai Nie (Asian Academy of Management Journal, 1999)
Islamic banking has become an increasingly popular source of innovation in international financial markets. Several prominent and financially strong Islamic bank have been established since the mid-Seventies and almost all have grown since the time of their origin. In Malaysia for example, the number of financial institutions which provide Islamic Banking products in addtion to conventional banking has increased from 17 in 1993 to 55 in 1995. Currently there are approximately 45 cou tries withsome form of Islamic banking or financial institutions and Islamic banking firms are loacted in countries ranging from Saudi Arabia, Bahrain, Turkey, and Bangladesh, to Switzerland, Denmark, and Luxembourg.